Table 3_Efferocytosis-associated genes serve as prognostic biomarkers for pancreatic ductal adenocarcinoma and identify P2RY6 as a therapeutic target.docx - Xiangjun Wang (2522917) (2025)
Background Pancreatic ductal adenocarcinoma (PDAC) is a highly malignant tumor with poor prognosis. Efferocytosis, an essential process for clearing apoptotic cells, is involved in shaping immunosuppressive microenvironment, facilitating tumor immune evasion. This study aims to evaluate the prognostic value of efferocytosis-related biomarkers in PDAC and elucidate their underlying mechanisms, providing insights for personalized therapy. Methods We integrated bulk and single-cell transcriptomic data from public database to construct and validate an efferocytosis-related prognostic model for PDAC. Additionally, we analyzed the specimens from a cohort of 81 PDAC patients alongside cell experiments to elucidate the function of P2RY6. RNA-seq analysis was employed to uncover the effector pathways mediated by P2RY6. Results An efferocytosis-based prognostic model, EFFscore, developed based on ADAM9, P2RY6, and CD36, can effectively assess the tumor phenotype of PDAC patients. The EFFscore is strongly associated with tumor evolution, malignant biological characteristics and microenvironmental interactions of PDAC. The essential mediator P2RY6 is significantly upregulated in PDAC tissue and cells, correlating closely with poor prognosis. Functional studies demonstrate that P2RY6 inhibition exhibits tumor-suppressive effects by activating the endoplasmic reticulum stress and enhancing anti-tumor immune responses. The P2RY6 receptor inhibitor, MRS-2578, emerges as a promising therapeutic candidate for PDAC treatment. Conclusion The prognostic model EFFscore exhibits remarkable predictive performance, accurately reflecting the malignant potential of PDAC. P2RY6 serves as a key oncogenic factor driver in PDAC, its targeted inhibition significantly suppresses tumor progression, highlighting its dual potential as a diagnostic biomarker and therapeutic target.